Arab-uprising: an analysis from political economy perspective - Pramanik, Ataul Huq (Emerald Group Publishing, 2014)
Purpose – This paper aims at examining the past as well as the current issues responsible for the most recent Arab-uprising. Design/methodology/approach – The empirical evidence based on regression and correlation together with tabular presentations suggests that the issue of Arab-uprising can be examined from both theoretical and factual evidence. Both theoretical and empirical findings testify the extremely high interrelationships existing among the determinants and co-determinants of Arab-uprising. Based on the three most fundamental pre-requisites for living a life with satisfaction based on personal honour, dignity, voice, peace, justice and equality of opportunity, the economic, political and socio-cultural components are found to be neglected in the Arab World. The constraint of data limited the scope to use systematically available and reliable independent variables, in particular, warranted by any sophisticated empirical model. Findings – The findings will have policy directions for the policy-makers/politicians to address the serious issues involving empowerments. It is argued that the ad hoc solution based on buying the dissent of the critics using handouts is not a long-term sustainable solution to the problems. The findings are also expected to create social consciousness among those who are most concerned to see the changes in the society for betterment where every citizen can stand for his honour, dignity and voice, justice and equality. Originality/value – It is expected that the general reader can understand the issues raised in this paper, internalize the ideas and create an overall environment to redirect the policy frameworks for resolving the social problems without conflict.